Juvenile justice - McCarter, Susan (Handbook of forensic social work, 2024)
This chapter highlights contemporary facets of forensic social work practice with juvenile justice-involved youth. Readers will consider the additional systems that many justice-involved youth contact (e.g., education, health/mental health care, substance abuse services, foster care); challenges to their biopsychosocial, spiritual, and cultural development; and their relevant subpopulation groups categorized by gender identity, LGBTQ+ identity, poverty status, and race/ethnicity. The chapter presents theoretical foundations in juvenile justice services and current treatment strategies with particular attention to youth development, wraparound service provision, reentry, trauma-informed care, culturally relevant interventions, and probation reform. The chapter concludes with an exploration of forensic social work settings and the role of social work with justice-involved youth along with a relevant case study featuring a young woman charged with assault with a deadly weapon at school.